Importance of quadratus lumborum muscle trigger point injection and prolotherapy technique for lower back and buttock pain - Sirh, Soo-Ji; Sirh, So-Woon; Mun, Hah-Yong; Sirh, Heon-Man (Frontiers in Pain Research, 2022)
Low back pain is a heterogeneous disease. Myofascial pain and enthesopathy of the quadratus lumborum muscle are important causes of lower back and/or buttock pain. However, a concrete, safe and effective injection technique for the treatment of trigger point and enthesopathy in the quadratus lumborum muscle has not yet been developed. We aimed to evaluate the importance of the quadratus lumborum muscle and to introduce an effective landmark-based blind injection technique for treating the quadratus lumborum muscle. Patients (n=17) with lower back and/or buttock pain were placed in the lateral decubitus position, and we delicately palpated the quadratus lumborum muscle to accurately locate its lesions, including trigger points, taut bands, and tendon lesions after five key landmarks had been identified. A newly designed 60–90-mm, 28-gauge thin hypodermic needle was inserted at the tender points. The needle was typically advanced until its tip touched the transverse process to treat myofascial trigger points and tendon lesions in the iliocostal, iliolumbar and lumbocostal fibers. Subsequently, lidocaine (0.5%) or a mixture of lidocaine (0.5%) and dextrose (12.5–15%) was injected. The pretreatment visual analog scale score in all seventeen patients decreased from ≥4–8/10 (mean 5.588) to 0–1/10 (mean 0.294) after the completion of all treatments. The total number of treatments was 1 to 4 in acute and subacute and 2 to 8 in chronic cases. For the first time, we describe a groundbreaking landmark-based integrated injection technique for the effective treatment of trigger points and myofascial pain in the quadratus lumborum.